2023
DOI: 10.3389/fmicb.2023.1111516
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin production enhancing mechanism of Lactiplantibacillus paraplantarum RX-8 response to Wickerhamomyces anomalus Y-5 by transcriptomic and proteomic analyses

Abstract: Plantaricin is a kind of bacteriocin with broad-spectrum antibacterial activity on several food pathogens and spoilage microorganisms, showing potential in biopreservation applications. However, the low yield of plantaricin limits its industrialization. In this study, it was found that the co-culture of Wickerhamomyces anomalus Y-5 and Lactiplantibacillus paraplantarum RX-8 could enhance plantaricin production. To investigate the response of L. paraplantarum RX-8 facing W. anomalus Y-5 and understand the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Consistent with our findings, some authors have also reported the isolation of Lpb. paraplantarum strains with biotechnological interest, including bacteriocin production, from spontaneously fermented foods such as fermented mushrooms, Chinese pickles, and Korean fermented foods [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our findings, some authors have also reported the isolation of Lpb. paraplantarum strains with biotechnological interest, including bacteriocin production, from spontaneously fermented foods such as fermented mushrooms, Chinese pickles, and Korean fermented foods [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…paraplantarum , recent studies have highlighted the capability of Lpb. paraplantarum RX-8, isolated from traditional pickles, to produce plantaricin, linked to its antibacterial activity [ 61 ]. Furthermore, other studies have highlighted the potential use of similar bacteriocinogenic strains of Lactiplantibacillus plantarum for animal nutrition, showing promising results in mitigating methane emissions in ruminants [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with W. anomalus Y-5 in mono-culture, W. anomalus Y-5 in co-culture suffered multiple stress including acid stress, osmotic pressure and absence of nutrients, which led to W. anomalus Y-5 growth slowly and cell number decline [14]. In the acid environment, the protein kinase A (PKA) pathway in yeast regulates cell death [20].…”
Section: Glucose Signaling Pathway Of W Anomalus Y-5 In Coculturementioning
confidence: 99%
“…In the previous study, we found that the co-culture of W.anomalus Y-5 and L. paraplantarum RX-8 could enhance plantaricin production [14]. The response mechanism of L. paraplantarum RX-8 facing W. anomalus Y-5 has been investigated.…”
Section: Introductionmentioning
confidence: 99%